THE IMPACT OF THE ENTREPRENEURIAL SUPPORT RELATIONSHIP ON THE LEARNING OF ENTREPRENEURS: AN EMPIRICAL ASSESSMENT WITH TUNISIAN NOVICE ENTREPRENEURS - Fitouri, Mohamed; Zouaoui, Samia Karoui (APPS Publications, 2021)
This paper examines the impact of the entrepreneurial coaching relationship on entrepreneurs' learning. We use the structural equation method with the partial least squares technique to test our hypotheses on a set of Tunisian novice entrepreneurs. The results are generally in line with theoretical predictions and highlight the key role that the coaching relationship plays in the learning of the entrepreneur.